Dwelling in times of COVID-19: An analysis on habitability and environmental factors of Spanish housing. (15th November 2022) - Navas-Martín, Miguel Ángel; Oteiza, Ignacio; Cuerdo-Vilches, Teresa
Abstract: In the wake of the SARS-CoV-2 pandemic, promoted by the World Health Organization (WHO), governments urged people to stay at home. For this reason, practically all human activity took place inside the houses. The research question established if housing quality responded to people's needs in the context of confinement. Specifically, the purpose was to taxonomize the dwelling stock occupied by confined households during the first COVID-19 wave in Spain, as well as to deepen in features and subjective perceptions on Indoor Environmental Quality (IEQ). As an exploratory study, an online questionnaire was disseminated in the Spring of 2020, obtaining 1, 673 valid responses. A descriptive statistical analysis included sociodemographic, territorial and housing variables, related to indoor environmental quality, the availability of outdoor spaces, and the prospects for changes in. Also, a logistic regression stablished multivariate relations for the dependent variable "general dwelling satisfaction". The results associated urban habitat, tenancy regime, higher incomes, and fewer cohabitants, with worse perceived IEQ, and lack of own outdoor space. Same variables showed relations with people's desire for domestic changes. In conclusion, it is remarkable the determining role of housing design for dwellers' satisfaction, especially in uncertain times like COVID-19 pandemic. This not only conditioned the different ways of inhabiting and occupying dwellings, but also the people's capacity to face lockdown. The built environment, the habitat, and households' circumstances also influenced. The latter did on people's perception of their experience, and how they lived and expressed it. Additionally, resilient building design and renovation opportunities were identified. Highlights: Spanish housing taxonomy in pandemic were identified for analysis and future design. Perceived indoor environmental quality was related to general dwelling-design features. People living in less than 90 m 2 experienced dissatisfaction during the pandemic. Type of dwelling and tenancy regime also showed significance in dissatisfaction. Policies and strategies such as renovate housing for affordable rental are boosted.